Empowering critical thinking skills by implementing scientific approach-based models among various students’ ethnics - Didimus Tanah Boleng; Elsje Theodora Maasawet; Krishna Purnawan Candra (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
In empowering students’ 21st century skills, the implementation of scientific approach-based models (SAbM) is recommended. This quasi-experimental research was conducted in senior high school in which the students were comprised of different ethnics. The aim of the study was to determine the effect of SAbM on empowering students' critical thinking skills (CTS). The SAbM implemented were Problem-Based Learning (PBL), Guided Inquiry (GI), and PBL+GI combination. Furthermore, the students’ ethnics included were Javanese, Bugis, Kutai, Banjar, and Toraja. The purposive sampling was used to determine the classes employed (i.e. 11th classes from two senior high schools in Samarinda). The instrument used to collect CTS data was questions test. The data were analyzed using two-way ANCOVA. The results showed that there was no significant interaction between ethnic and learning models on the students' CTS (p = 0.219), as also shown by the main effect of ethnic types (p = 0.583). In contrast, there was a significant effect of SAbM on students’ CTS (p = 0.0005) Through this study, SAbM need to be implemented continuously as it can optimize the empowerment of students’ 21st Century skills.